Multicolor flow cytometry-based cellular phenotyping identifies osteoprogenitors and inflammatory cells in the osteoarthritic subchondral bone marrow compartment. Issue 11 (November 2015) - Pippenger, B.E.; Duhr, R.; Muraro, M.G.; Pagenstert, G.I.; Hügle, T.; Geurts, J.
Summary: Purpose: The cellular component of subchondral bone is thought to be responsible for aberrant bone remodeling in osteoarthritis (OA). Direct phenotypical analysis of the cellular compartment is critical to better understand the OA disease process. This study provides proof-of-principle for flow cytometry-based phenotyping of isolated subchondral trabecular bone (STB) marrow cells without prior use of cell culture techniques. Methods: Tibial plateaus were obtained from OA patients undergoing total knee arthroplasty. Subchondral bone chips were digested with collagenase IA and single cell suspensions were directly phenotyped using flow cytometry. Cells were analyzed for the expression of alkaline phosphatase (ALP) as osteoblast/osteoprogenitor marker and monocyte/macrophage markers (CD14, CD68, HLA-DR, CD115). Results: MTT staining revealed abundant viable cells in the bone marrow compartment of STB prior to digestion, which were efficiently released by collagenase. Within the CD45-negative cell fraction, approximately 20% of the cells were positive for the early osteoblast/osteoprogenitor marker ALP. Within the CD45+ hematopoietic cell fraction, the majority of cells were of monocytic origin (>80%) displaying strong surface expression of CD14. Discreet macrophage populations (CD14+/HLA-DR+/CD68+) and putative osteoclast progenitors (CD45+/HLA-DR−/CD115+) were unequivocally identified. Osteoblast, macrophage and osteoclast progenitor presence in the subchondral bone unit (SBU) was confirmed by (immuno)histochemical staining for osteocalcin, CD68 and tartrate-resistant acid phosphatase, respectively. Conclusions: Flow cytometric analysis is a valuable methodology to study the cellular compartment of STB marrow. This method provides a proof of principle that the whole resident cell population can be directly phenotypically characterized without the prior use of cell culture techniques.